Legal Strength of Electronic Certificates in Land Sale and Purchase Agreements in Indonesia - Novianti, Elisa (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
The digital transformation in the land sector, realized through the issuance of electronic land certificates by the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN), has significant legal implications, particularly in land sale and purchase agreements. This study aims to analyze the legal force of electronic land certificates as evidence in land sale and purchase transactions in Indonesia. The research uses a normative juridical method with a statutory and literature approach. The results show that electronic land certificates have equal legal standing with physical certificates, as regulated in Ministerial Regulation of ATR/BPN No. 1 of 2021 and No. 3 of 2023. Electronic certificates fulfill the criteria as authentic written evidence and are legally valid as long as the registration process follows the applicable laws and regulations. However, their implementation still faces challenges, including digital infrastructure limitations, public awareness, and potential administrative disputes.